Prevalence and clinical correlates of pathological affective display in Alzheimer's disease. Issue 1 (July 1995) - Starkstein, S E; Migliorelli, R; Tesón, A; Petracca, G; Chemerinsky, E; Manes, F; Leiguarda, R
Abstract : This study examined the prevalence and correlates of pathological affect in Alzheimer's disease. A consecutive series of 103 patients with Alzheimer's disease were examined with a comprehensive psychiatric assessment that included the pathological laughing and crying scale (PLACS). Forty patients (39%) showed pathological affect: 25% showed crying episodes, and 14% showed laughing or mixed (laughing and crying) episodes. Patients with pathological affect crying showed significantly higher depression scores and a significantly higher frequency of major depression and dysthymia than patients with no pathological affect. Patients with mixed pathological affect showed significantly more subcortical atrophy on CT than patients with pathological affect crying. Forty seven per cent of the patients with pathological affect had no congruent mood disorder, and they showed a significantly longer duration of illness and more severe anosognosia than patients with pathological affect that was congruent with an underlying mood disorder. The study validates the PLACS, and shows the high prevalence of pathological affect in Alzheimer's disease.